Strategi Marketing Kain Ihram, Masa Kini Dan Masa Depan Di Industri Kreatif - Taufik Reza Oktavenda; Syarifah Gustiawati; Indriya . (CV. ITTC INDONESIA, 2024)
This study examines the marketing strategy of Naga Paksi's Ihram fabric brand in Bogor City for both current and future prospects within the creative industry. With a Muslim population reaching 242 million, domestic demand for Ihram fabric can reach 5 million meters per year, with 70% of this demand relying on imports. In response to this phenomenon, the Naga Ihram fabric brand was developed as a result of research funded by the LITAPDIMAS grant from the Indonesian Ministry, tested in the lab for halal certification, and is an advancement from Ihram Halal, which won the Bogor Innovation Award 2023 and holds a patent. A qualitative research method with a descriptive approach is used to understand the phenomena experienced by the Naga Paksi brand. Through SWOT analysis, this study identifies strengths related to product integrity, weaknesses such as an undeveloped marketing team and a nascent business level, opportunities such as a large market and dependency on imports, and threats such as competition from imported products and economic fluctuations. This information is then aligned with various relevant and current literature to develop marketing strategy recommendations for the creative industry era. Thus, it is expected that the Naga Paksi brand will contribute to strengthening the Islamic economy and textile industry independence in Indonesia. Keywords: Ihram Fabric, Marketing Strategy, and Creative Industry.